2000
DOI: 10.1034/j.1600-0455.2000.041002125.x
|View full text |Cite
|
Sign up to set email alerts
|

IMAGING OF AORTOILIAC ARTERIAL DISEASE. Duplex ultrasound and MR angiography versus digital subtraction angiography

Abstract: Purpose: To evaluate and compare the diagnostic accuracy of duplex ultrasound (US) and MR angiography (MRA) at 1.0 T in aortoiliac arterial disease using digital subtraction angiography (DSA) as the reference standard. In addition, a comparison of the 2D time‐of flight (TOF) and 3D contrast‐enhanced MRA (CE MRA) techniques was performed. Material and Methods: Prospectively, 39 patients with symptoms of lower‐extremity arterial occlusive disease were examined using US, TOF MRA, CE MRA and DSA. Significant lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 0 publications
2
15
1
2
Order By: Relevance
“…In both studies, results similar to those observed in the current study were reported: sensitivities and specificities of duplex US of 72% and 88%, respectively (21), and of 72% and 97%, respectively (22). Sensitivities and specificities of contrast-enhanced MR angiography were 81% and 86%, respectively (21), and 88% and 92%, respectively (22). In the study by Wikstrom et al (21), however, there was considerable selection bias because nonconsecutive patients with iliac artery stenosis found at duplex US also underwent contrast-enhanced MR angiography and intraarterial DSA.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In both studies, results similar to those observed in the current study were reported: sensitivities and specificities of duplex US of 72% and 88%, respectively (21), and of 72% and 97%, respectively (22). Sensitivities and specificities of contrast-enhanced MR angiography were 81% and 86%, respectively (21), and 88% and 92%, respectively (22). In the study by Wikstrom et al (21), however, there was considerable selection bias because nonconsecutive patients with iliac artery stenosis found at duplex US also underwent contrast-enhanced MR angiography and intraarterial DSA.…”
Section: Discussionsupporting
confidence: 91%
“…Thus far, two studies (21,22) in which duplex US was compared with contrastenhanced MR angiography in the same patients have been published. In both studies, results similar to those observed in the current study were reported: sensitivities and specificities of duplex US of 72% and 88%, respectively (21), and of 72% and 97%, respectively (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although phase contrast MRA was superior to time of light (TOF) MRA, the most accurate results were achieved when the two methods were combined (4).…”
Section: Introductionmentioning
confidence: 93%
“…16-Zeilen-Technik stellen eine ernst zu nehmende Alternative zur intraarteriellen digitalen Subtraktionsangiographie (i.a. DSA) vor allem der proximalen Extremitätenstrombahn dar [15,16]. Die Wertigkeit insbesondere der MR-Angiographie wird an anderer Stelle in diesem Heft vorgestellt.…”
Section: Nichtinvasive Radiologische Verfahrenunclassified